Rent appropriation of knowledge-based assets and firm performance when institutions are weak: A study of Chinese publicly listed firms - QIAN, Cuili (Institutional Knowledge at Singapore Management University, 2017)
A firm's strategic investments in knowledge-based assets through research and development (R&D) can generate economic rents for the firm, and thus are expected to affect positively a firm's financial performance. However, weak protection of minority shareholders, weak property rights, and ineffective law enforcement can allow those rents to be appropriated disproportionately by a firm's powerful insiders such as large owners and top managers. Recent data on Chinese publicly listed firms during 2007-2012 were used to demonstrate that the expected positive relationship between knowledge assets and performance is weaker in transition economies when a firm's ownership is highly concentrated and its managers have wide discretion. Moreover, rent appropriation by insiders was shown to vary with the levels of institutional development in which a firm operates.